Stinky Little Skunk : Copycat Coloring - Alicia Sutandar
Color Stinky Little Skunk and friends with beautiful examples provided. The animals in this coloring book are from the book Stinky Little Skunk & Others Stories, written by 8-year old Alicia Sutandar. Also available Stinky Little Skunk Activity Book